Compilation of canthariphilous insects. - Hemp, Claudia; Dettner, Konrad (Contributions to Entomology = Beiträge zur Entomologie, 2001)
A list of insects attracted to cantharidin is given. Most canthariphilous insects are found within the heteromeran beetle family Anthicidae with 185 species in the three subfamilies Anthicinae (179), Lemodiinae (1) and Tomoderinae (5). Further cantharidin baited species are known from the beetle families Endomychidae (5), Cleridae (4), Chrysomelidae (3), and Staphylinidae (1). In the beetle family Pyrochroidae 23 species from the subfamily Pedilinae and 6 species of the Pyrochroinae are canthariphilous. The insect order Diptera is represented by the families Anthomyiidae (3), Cecidomyidae (2), Ceratopogonidae (22) Chloropidae (1), Platystomatidae (1) and Sciaridae (5). Many species from the heteropteran family Miridae (29) are known to be attracted by cantharidin, also one species from the families Lygaeidae and Tingidae respectively. Parasites of the hymenopteran family Braconidae (6) show a positive reaction to cantharidin as well as species from the subfamily Diapriinae of the family Diapriidae. Chemical analyses of a fulgorid and a cicadid species revealed that also species of Homoptera may contain cantharidin.Keywordscantharidin, canthariphilous insects, Coleoptera, Diptera, Heteroptera, Homoptera.